PASTORAL KONSELING: DESKRIPSI UMUM DALAM TEORI DAN PRAKTIK - Widodo Gunawan (Sekolah Tinggi Theologia Abdiel, 2018)
Pastoral Counseling is a holistic service that everyone needs. Therefore, the science of pastoral counseling must continue to open up to other sciences, so that pastoral care counseling can provide more accountable services from many aspects. With regard to the science of counseling that continues to grow, also need to be balanced with competent human resources who can be a driving force to achieve effective results.